Digital Health Interventions to Promote Physical Activity in Community-Dwelling Older Adults: A Systematic Review and Semiquantitative Analysis - M. Di Pumpo; M. Di Pumpo; A. Miatton; M. T. Riccardi; M. T. Riccardi; E. A. Graps; V. Baldo; A. Buja; G. Damiani; G. Damiani (International Journal of Public Health)
ObjectivesPhysical activity (PA) is crucial for older adults’ wellbeing. Digital health interventions (DHIs) are important, however a synthesis aimed at healthy community-dwelling OA is lacking. This study aims to synthesize DHIs effect on PA levels among community-dwelling 60-year-old adults or older.MethodsA systematic review was performed. DHIs using eHealth/mHealth tools, apps and text messaging were included. Primary outcomes were daily steps, moderate-to-vigorous PA and sedentary time. Quality was assessed via Cochrane risk-of-bias tools. Study-reported effect, study quality, sample size, study duration and dropout rate were semi-quantitatively synthesized to determine the overall category effect.Results12 studies were included. 75% were low-quality, sample size was 16–18,080, study duration was 3–18 weeks, average dropout rate was 4.2%–46.7%. The synthesis of “motivational reminders” and “dynamic exercise programs” showed an overall positive effect, of “PA self-monitoring” showed mixed results and “exercise digital coaching” showed a non-positive effect.DiscussionMotivational reminders and dynamic exercise programs proved more effective in increasing PA in older adults than other interventions and should be more embedded in structured public health programs.